Influence of media in eating habits of children: a sistematic review - Mariane de Oliveira Milani; Letícia Garlet; Gabriela Guareschi Romero; Karen Mello de Mattos (Universidade de Santa Cruz do Sul, 2015)
Background and Objectives: Inadequate eating habits can lead to problems of development and growth among children. The aim of this study was to review the literature assessing the influence of the media on child feeding. Content: Twenty national and international publications were selected, being both original and review articles in Portuguese and English from 2010 in Pubmed, Bireme and Scielo data from pre-selected descriptors were searched. Conclusion: Media is a strong influencer in food choices of children, that food advertisements are basically unhealthy products and that haven'teffective control by regulatory standards. KEYWORDS: Child. Food publicity. Television.